Effects of Land Use Changes on CO2 Emission Dynamics in the Amazon - Rocha, Adriano Maltezo da [UNESP]; Franceschi, Mauricio; Panosso, Alan Rodrigo [UNESP]; Carvalho, Marco Antonio Camillo de; Moitinho, Mara Regina [UNESP]; Martins Filho, Marcílio Vieira [UNESP]; Oliveira, Dener Marcio da Silva; Freitas, Diego Antonio França de; Yamashita, Oscar Mitsuo; La Scala, Newton [UNESP] (MDPI, 2025)
Global climate change is closely tied to CO2 emissions, and implementing conservation-agricultural systems can help mitigate emissions in the Amazon. By maintaining forest cover and integrating sustainable agricultural practices in pasture, these systems help mitigate climate change and preserve the carbon stocks in Amazon forest soils. In addition, these systems improve soil health, microclimate regulation, and promote sustainable agricultural practices in the Amazon region. This study aimed to evaluate the CO2 emission dynamics and its relationship with soil attributes under different uses in the Amazon. The experiment consisted of four treatments (Degraded Pasture—DP; Managed Pasture—MP; Native Forest—NF; and Livestock Forest Integration—LF), with 25 replications. Soil CO2 emission (FCO2), soil temperature, and soil moisture were evaluated over a period of 114 days, and the chemical, physical, and biological attributes of the soil were measured at the end of this period. The mean FCO2 reached values of 4.44, 3.88, 3.80, and 3.14 µmol m−2 s−1 in DP, MP, NF, and LF, respectively. In addition to the direct relationship between soil CO2 emissions and soil temperature for all land uses, soil bulk density indirectly influenced emissions in NF. The amount of humic acid induced the highest emission in DP. Soil organic carbon and carbon stock were higher in MP and LF. These values demonstrate that FCO2 was influenced by the Amazon land uses and highlight LF as a low CO2 emission system with a higher potential for carbon stock in the soil.
Keywords: carbon stock; degraded pasture; greenhouse gases; livestock forest; soil respiration